1989
DOI: 10.1128/mcb.9.2.594
|View full text |Cite
|
Sign up to set email alerts
|

A ras-dependent pathway abolishes activity of a muscle-specific enhancer upstream from the muscle creatine kinase gene.

Abstract: Differentiation of skeletal myoblasts is accompanied by induction of a series of tissue-specific genes whose products are required for the specialized functions of the mature muscle fiber. The program for myogenic differentiation is subject to negative control by several peptide growth factors and by the products of mutationally activated ras oncogenes, which persistently activate intracellular cascades normally triggered by specific growth factors. Previously, we reported that induction of the muscle creatine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…This finding was similar to our previous results with an H-ras-transfected myogenic derivative from the C3H1OT1/2 cell line, where even in the presence of six copies of an actively transcribed H-ras gene, the muscle phenotype was maintained and could be enhanced by 5-azacytidine treatment (18). These results suggest that increased MyoDI expression may be able to overcome a ras-mediated block to the induction of musclespecific genes (34). A recent report that a TrpE-MyoDl fusion protein specifically binds to the mck 5' enhancer (J.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…This finding was similar to our previous results with an H-ras-transfected myogenic derivative from the C3H1OT1/2 cell line, where even in the presence of six copies of an actively transcribed H-ras gene, the muscle phenotype was maintained and could be enhanced by 5-azacytidine treatment (18). These results suggest that increased MyoDI expression may be able to overcome a ras-mediated block to the induction of musclespecific genes (34). A recent report that a TrpE-MyoDl fusion protein specifically binds to the mck 5' enhancer (J.…”
supporting
confidence: 81%
“…Other studies have approached the question of the relationship between differentiation and transformation in muscle cells by the introduction of transforming ras genes into myoblast cell lines (18,28,34). These experiments have shown that activated N-ras or H-ras genes can prevent skeletal myoblast differentiation in some (28) but not all (18) mouse cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have reported previously that the mck enhancer is contained within the region between bp -1350 and -1048 5' of the mck transcription initiation site (14,24,27,52,53). As a first step toward identification of nuclear factors that interact with the mck enhancer region, we divided the 302-bp enhancer into two parts by digestion with AvaI and analyzed factor interactions within each part by using gel retardation assays.…”
Section: Resultsmentioning
confidence: 99%
“…Reporter plasmids for muscle-specific transcription included the pMCK-CAT plasmid (Sternberg et al, 1988), the 4R-tkCAT reporter (Weintraub et al, 1990), and the myogenin reporter construct pMyo1565CAT (kindly provided by E.N. Olson, University of Texas Southwestern Medical Center, Dallas, TX).…”
Section: Transient Transfections and Chloramphenicol Acetyl Transferamentioning
confidence: 99%